Challenges and opportunities of the radio industry. Public radio case of Ecuador - Londoño Proaño, Cristián (2024)
Radios face significant challenges in the face of digital transformation. The purpose of this study, based on the current state of the radio industry, is to analyze the opportunities and challenges that digitalization presents for traditional radio stations and public radio in Ecuador. It uses a qualitative methodology, where it explores various indicators and trends in the contemporary radio ecosystem. The results show that, although the funding and prominence of public radio has decreased over time, the digital transformation opens doors to connect with younger audiences and to diversify the content offered. In addition, the potential of new digital formats and platforms is highlighted. The conclusions highlight the imperative need for radio stations to reconfigure and adapt to this constantly changing landscape, if they want to ensure their relevance and sustainability in the near future.